A descriptive study of the community-based follow-up and outcomes of very low birth weight babies discharged from a regional hospital - Gondwana de Wit, Thandi Maya (Department of Paediatrics and Child Health, 2023)
Background Neonatal mortality continues to be a significant global health concern, especially in low/middle income countries. In South Africa, neonatal deaths contribute to 32% of the under-five mortality rate, with 48% of these deaths attributed to prematurity. One of the components aimed at reducing neonatal deaths in the Western Cape, is the Home and Community-Based Services (HCBS) for very low birth weight (VLBW) babies. This intervention could reduce neonatal deaths by 25%. This study aimed to describe a VLBW baby cohort discharged from a regional hospital in Cape Town over a year; the HCBS referral process; their follow-up; their outcomes and caregivers' perceptions of the service. Methods This was a retrospective descriptive mixed methods study. Quantitative data from an accredited database were used to describe the VLBW cohort. Meetings with stakeholders and referral form analyses were used to assess the referral pathway and follow-up. Telephonic interviews were held with VLBW babies' caregivers to obtain further quantitative and qualitative data about the HCBS programme. Results During 2018, 169 VLBW babies were included in the population with a mean (SD) gestational age of 30 (±2.21) weeks and median (IQR) birthweight of 1210g (1045-1390g). At delivery, 84.6% had respiratory distress with 60% requiring continuous positive airway pressure; 64% had presumed and 15.3% had suspected or proven nosocomial sepsis. Caregiver characteristics included unbooked pregnancies (10%), primigravida deliveries (15%), smoking (11%), maternal alcohol use (9%), teenage pregnancy (5%), drug addiction (3%) and babies born before hospital arrival (4%) with 14% being referred to a social worker. Folder review showed plans for HCBS referral in only 49 (43.4%) of the cohort, however only 20 (17.7%) referral forms were received by HCBS. Learning about the VLBW HCBS programme identified several challenges relating to the referral process from both the hospital and HCBS side. Overall, the caregivers interviewed had positive perceptions of the HCBS. Those not visited by HCBS felt they would have benefitted from a visit. Conclusion The burden of this medically and socially vulnerable VLBW cohort, who are at high risk of neonatal mortality and morbidity, remains large at this regional hospital - constituting nearly 15% of all their neonatal discharges. Despite the identified challenges, the caregivers' interviewed remained positive about the HCBS. HCBS can play an essential role in providing education, counselling and support following hospital discharge. However, for the HCBS to be fully effective, further promotion, strengthening and monitoring of the referral system is required.